HUBUNGAN INTERAKSI SOSIAL DAN HARGA DIRI DENGAN KOHESIVITAS KELOMPOK PADA SISWA SEKOLAH SEPAKBOLA (SSB) DI KUDUS - Mikail Ahabba; Mochamad Widjanarko; Mohammad Khasan (Jurnal Psikohumanika, 2021)
This study aims to determine the relationship of social interaction and self-esteem with group cohesiveness of SSB students in Kudus. The subjects of this study were 80 students of SSB in Kudus. The sampling technique in this study used a quota sampling technique. The measuring tools used to obtain the data are the social interaction scale, self-esteem scale, and group cohesiveness scale. The results of data analysis using Regression Analysis where the calculation uses the SPSS 15.0 program. The results of the correlation coefficient rx1,2y of 0.836 with p of 0.000 (p<0.01) mean that there is a very significant relationship between social interaction and self-esteem with group cohesiveness. The result of the correlation coefficient between social interaction variables and group cohesiveness rx1y is 0.836 with p of 0.000 (p <0.01) this means that there is a very significant positive relationship between social interaction and group cohesiveness. While the correlation coefficient between the variable self-esteem and group cohesiveness rx2y is 0.708 with p of 0.000 (p <0.01) this means that there is a very significant positive relationship between self-esteem and group cohesiveness. The effective contribution of the independent variable to the dependent variable is 69.9%.